Changes in dietary intake of aspartic acid during and after intermittent fasting correlate with an improvement in fasting glucose in overweight individuals. Issue 2 (9th January 2023) - Karras, Spyridon N.; Koufakis, Theocharis; Dimakopoulos, Georgios; Popovic, Djordje S.; Kotsa, Kalliopi
Abstract : Highlights We investigated a potential correlation between amino acid intake and glycemic markers among individuals who practiced intermittent fasting and controls. Reduced aspartic acid intake during and after intermittent fasting presented a positive correlation with fasting glucose. The positive effects of intermittent fasting on glucose metabolism could be partially related to a decrease in the ingestion of specific amino acids.